2009
DOI: 10.1093/plankt/fbp073
|View full text |Cite
|
Sign up to set email alerts
|

Variation in diatom biochemical composition during a simulated bloom and its effect on copepod production

Abstract: Variation in diatom biochemical composition during a simulated bloom and its effect on copepod production The biochemical quality of phytoplankton depends in part upon nutrient availability, which has implications for the population dynamics of grazers. Here, we examined how nutrient availability influenced the growth dynamics and biochemical content of the marine diatom Thalassiosira weissflogii and how these biochemical changes impacted the vital rates of a calanoid copepod (Acartia tonsa). Changes in bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 65 publications
2
18
0
2
Order By: Relevance
“…Changes in molar amino acid composition can also be related to the diatoms' requirements for different amino acids under different growth conditions. Several studies have reported that diatoms change their protein content in response to higher temperatures, nutrient availability and salinity (Rousch et al, 2003;Araujo and Garcia, 2005;Diekmann et al, 2009). Given the large ecological role of marine diatoms, it is evident from such data that the high macromolecular plasticity of individual diatom species such as T. weissflogii has the potential to alter nutrient and energy fluxes in marine ecosystems (Sackett et al, 2013).…”
Section: Sensitivity Of δ 13 C Aa Patterns To Algal Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in molar amino acid composition can also be related to the diatoms' requirements for different amino acids under different growth conditions. Several studies have reported that diatoms change their protein content in response to higher temperatures, nutrient availability and salinity (Rousch et al, 2003;Araujo and Garcia, 2005;Diekmann et al, 2009). Given the large ecological role of marine diatoms, it is evident from such data that the high macromolecular plasticity of individual diatom species such as T. weissflogii has the potential to alter nutrient and energy fluxes in marine ecosystems (Sackett et al, 2013).…”
Section: Sensitivity Of δ 13 C Aa Patterns To Algal Growth Conditionsmentioning
confidence: 99%
“…To address the question of whether δ 13 C AA patterns of phytoplankton remain constant under varying environmental conditions, we cultured Thalassiosira weissflogii under controlled conditions. Thalassiosira weissflogii is an abundant, nitrate-storing, bloom-forming diatom with high phenotypic plasticity, i.e., the ability to change macromolecular composition (Diekmann et al, 2009;Kamp et al, 2013). Diatoms are a diverse and ecologically important group contributing up to 40 % of the ocean's primary production (Nelson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The methods employed were the same as those discussed by Diekmann et al (2009), examining different algal treatments on EPR except for the following changes. First, EPR and HS are presented from control groups of copepods-those fed with algae maintained in exponential growth-phase.…”
Section: Laboratory Datamentioning
confidence: 99%
“…Not only food quantity but also quality (size, biochemical composition) are critical features affecting growth and reproductive success of calanoid copepods (e.g. Houde and Roman 1987, study site: Chesapeake Bay; Dutz et al 2008, copepods from the North Sea; Diekmann et al 2009). To better understand the role of phytoplankton as a controlling factor of copepod production, studies of food quality at our study site are needed.…”
Section: Reproductive Rate and Survivalmentioning
confidence: 99%
“…In variable environments, such as those in the Southern Ocean, the caloric value of food can be of critical importance, in particular in winter when sunlight and food are scarce. For example, lipids, which are the most energy-rich macromolecule, are known to vary under different environmental conditions (Mock and Kroon, 2002); therefore, changes in macromolecular composition and energy partitioning in the cell will determine the nutritional value of the food and productivity of the entire food web (Diekmann et al, 2009). Quantifying a species' capacity for phenotypic variation can inform predictions of its ability to survive environmental change (Charmantier et al, 2008) and may provide insight into which species could dominate under future environmental conditions in the Southern Ocean, such as a reduction in sea-ice thickness, duration and extent.…”
Section: Introductionmentioning
confidence: 99%